Complaints as starting point for vicious cycles in customer–employee-interactions - Traut-Mattausch, Eva; Wagner, Sara; Pollatos, Olga; Jonas, Eva (Frontiers in Psychology, 2015)
A ring-model of vicious cycles in customer-employee-interaction is proposed: Service employees perceive complaints as a threat to their self-esteem resulting in defense responses such as an increased need for cognitive closure, a devaluation of the customer and their information and degrading service behavior. Confronted with such degrading service behavior, customers react defensively as well, by devaluing the employee for example with regard to his/her competence and by reducing repurchase and positive word-of-mouth. Three studies investigated each link in this ring-model. In study 1, participants were confronted with an aggressive or neutral customer complaint. Results show that motivated closed-mindedness (one aspect of the need for cognitive closure) increases after an aggressive complaint leading to a devaluation of the customer and their information, and in turn to a degrading service reaction. In study 2, participants were confronted with a degrading or favorable service reaction. Results show that they devaluate the employees’ competence after receiving a degrading service reaction and thus reduce their intention to repurchase. In study 3, we finally examined our predictions investigating real customer-employee-interactions: We analyzed data from an evaluation study in which mystery callers tested the service hotline of an airline. Results show that the employees’ competence is devaluated after degrading behavior and thus reduces positive word-of-mouth.